189k views
5 votes
Could use some help please and thank you quickly tho it’s timed

Could use some help please and thank you quickly tho it’s timed-example-1

1 Answer

7 votes

Answer:

option c)

d = 1

Explanation:

Given the equation in the question,

-3d / (d² - 2d - 8) + (3 / d-4) = (-2 / d+2)

quadratic factorisation

-3d / (d+2)(d-4) + (3 / d-4) = (-2 / d+2)

-3d / (d+2)(d-4) = (-2 / d+2) - (3 / d-4)

taking LCM on right side

-3d / (d+2)(d-4) = ( -2(d-4) - 3(d+2)) / (d+2)(d-4)

canceling (d+2)(d-4) on both sides

-3d = -2(d-4) - 3(d+2)

-3d = -2d + 8 - 3d - 6

-3d + 2d + 3d = 8 - 6

2d = 2

d = 1

User Dornathal
by
5.8k points